EFFECT OF WATER FLUID ON THE ELASTIC WAVE VELOCITY, POROSITY, AND PERMEABILITY OF AMPHIBOLITE DURING PARTIAL MELTING AT TEMPERATURES OF UP TO 850°C AND A PRESSURE OF 300 MPA: PHYSICOCHEMICAL APPROACH - Lebedev E.B. (My University, 2003)
The P- and S-wave velocities and their anisotropy in amphibolite samples were measured under a gas and water fluid pressure of 300 MPa and temperatures of up to 850°C. The experiments were carried out under equal fluid and confining pressure. The results of the experiments under water pressure drastically differ from those obtained under gas pressure. A minimum of elastic wave velocity in amphibolite was detected at a temperature of ∼650°C under wet conditions. This minimum reflects a velocity reversal caused by compaction. It was established that the variation in the elastic properties of the rock was controlled by modification of its microstructure. Processes of two types are responsible for the structural change of pore space in amphibolite: (1) phase transformation (α-β-transition in quartz) at 652°C and 300 MPa and (2) partial melting (up to 0.5-1.0 vol % of liquid phase at 705-808°C and 300 MPa. The variable microstructure is attributed to the formation of dilatant microfractures and local mass transfer. An increase in the velocity after passing a minimum can be caused by the sealing of microfractures with redeposited silicate material and filling with melt at a higher temperature. The elastic wave anisotropy in amphibolite under a water pressure of 300 MPa and a temperature reaching 850°C remains approximately constant (10%) and equals that under confining pressure in dry conditions. Hence, the elastic wave anisotropy in amphibolite is controlled by the orientation of its major minerals. The P- and S-wave velocities in amphibolite measured on a multianvil apparatus at 600 MPa and a temperature attaining 700°C (dry conditions) are reported for comparison.